ELECTRONIC LIBRARY AS AN OBJECT OF EDUCATIONAL TECHNOLOGIES - Kirichek, G. G. (Radio Electronics, Computer Science, Control, 2024)
The aim of investigation is determination of the main foundations and directions of development of electronic library, technological definition of principles and sources of acquisition for providing of creation of electronic library.